Respuesta :

Answer:

[tex]f(x)+g(x)=5x^{3} +4x^{2}+x-8[/tex]

Step-by-step explanation:

Given:

Two functions are given:

[tex]f(x)=5x^{3} +3x^{2} -3[/tex]

[tex]g(x)=x^{2} +x-5[/tex]

Find [tex]f(x)+g(x)[/tex]

Solution:

[tex]f(x)+g(x)=(5x^{3} +3x^{2} -3)+(x^{2} +x-5)[/tex]

[tex]f(x)+g(x)=5x^{3} +3x^{2} -3+x^{2} +x-5[/tex]

[tex]f(x)+g(x)=5x^{3} +(3x^{2} +x^{2})+x-3-5[/tex]

[tex]f(x)+g(x)=5x^{3} +4x^{2}+x-8[/tex]

Therefore, the function of [tex]f(x)+g(x)=5x^{3} +4x^{2}+x-8[/tex]

ACCESS MORE